Chemical constituents from the leaves of Pseuderanthemum tunicatum (Afzel.) Milne-Redhead (Acanthaceae). (February 2018) - Ndjateu, Fabrice S.T.; Tene, Mathieu; Shafi, Sarah; Siddiqui, Hina; Tane, Pierre; Choudhary, Muhammad I.
Abstract: Phytochemical study of the ethanol extract of the leaves of Pseuderanthemum tunicatum afforded eleven known compounds including madagascin (1 ), harunganol B (2 ), eicosanoic acid (3 ), dotriacontanoic acid (4 ), friedelin (5 ), lupeol (6 ), β-sitosterol (7 ), stigmasterol (8 ), β-sitosterol 3- O -β-d -glucopyranoside (9 ), stigmasterol 3- O -β-d -glucopyranoside (10 ) and apigenin 7- O -β-d -glucopyranoside (11 ). Acetylation of compound1 afforded madagascin diacetate (1a ), described here for the first time. The structures were established by interpretation of their spectral data, including IR, UV, MS, 1D- and 2D- NMR ( 1 H, 13 C, DEPT 135, 1 H– 1 H COSY, HMQC, HMBC and NOESY), as well as by comparison with literature data. In the present study all the compounds are isolated for the first time from the species P. tunicatum . Compounds1 and2 have never been reported from the Acanthaceae family. Compounds4 and6–11 have been previously isolated from the genus Pseuderanthemum, and compounds3 and5 from the family Acanthaceae. The chemotaxonomic significance of the isolated compounds is discussed. Highlights: No phytochemical study was previously reported on Pseuderanthemum tunicatum. All the compounds were isolated for the first time from Pseuderanthemum tunicatum . The chemotaxonomic significance of the isolated compounds is discussed. Fats, flavonoids, triterpenes and sterols might serve as chemotaxonomic markers for the genus Pseuderanthemum